2014
DOI: 10.1371/journal.pone.0098736
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of α2- and β-Adrenergic Receptor Stimulation on Quiescent Neural Precursor Cell Activity and Adult Hippocampal Neurogenesis

Abstract: Norepinephrine regulates latent neural stem cell activity and adult hippocampal neurogenesis, and has an important role in modulating hippocampal functions such as learning, memory and mood. Adult hippocampal neurogenesis is a multi-stage process, spanning from the activation and proliferation of hippocampal stem cells, to their differentiation into neurons. However, the stage-specific effects of noradrenergic receptors in regulating adult hippocampal neurogenesis remain poorly understood. In this study, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 42 publications
(58 reference statements)
3
39
0
2
Order By: Relevance
“…These high densities of α 2 -adrenergic receptors remain near the ventricular surface long after all cortical neurons have been generated [58]. Furthermore, stimulation of α 2 -adrenergic receptors increases nestin-positive cells in the mouse cortex [59], inhibits hippocampal neural precursor cell activity, and decreases hippocampal neurogenesis [60]. Our study found that NSCs harvested from embryonic rats and grown in vitro expressed α 2A -adrenoceptor.…”
Section: Discussionmentioning
confidence: 62%
“…These high densities of α 2 -adrenergic receptors remain near the ventricular surface long after all cortical neurons have been generated [58]. Furthermore, stimulation of α 2 -adrenergic receptors increases nestin-positive cells in the mouse cortex [59], inhibits hippocampal neural precursor cell activity, and decreases hippocampal neurogenesis [60]. Our study found that NSCs harvested from embryonic rats and grown in vitro expressed α 2A -adrenoceptor.…”
Section: Discussionmentioning
confidence: 62%
“…The aim of this approach was to identify key transcriptional changes underlying the decline in the activity and loss of competence of NSCs that occurs in adulthood, which is attributed to the combined up-regulation of inhibitory and down-regulation of positive cues [30], and is critical for the response of NSCs to brain injury and degeneration [31,32]. In this manner, key small molecules were identified for “rejuvenating” adult NSC (Fig 2E; Table 1D), approximately 20% of which overlapped with those required in dorsalizing or ventralizing the postnatal SVZ, and were categorized as “Receptor antagonist,” “Signaling,” and “Metabolism.” Some interesting candidates included antagonists for α/β adrenergic receptors, including the highly ranked nadolol (Table 1D), which have been described to promote NSC activation from quiescence in the dentate gyrus [33] and enhance NP survival following exit from the SVZ [34]. A key signaling pertubagen was monensin, which impedes TGFβ processing [35], a major neurogenesis inhibitory factor during aging [36].…”
Section: Resultsmentioning
confidence: 99%
“…55,56 However, subsequent studies using AR agonists and antagonists showed complex actions of the various AR systems: Stimulation of α2-ARs decreases while stimulation of β-AR enhances hippocampal NPC proliferation and neurogenesis. 34,57,58 Although the β-AR subtype selectivity of these effects remained unclear from the animal studies, cell cultures studies on adult hippocampal NPCs strongly suggest that NE regulation of adult hippocampal neurogenesis is mediated through β2-AR and/or β3-AR subtype. 58,59 These data strongly show the necessity of studies addressing the direct actions of the endogenous compound NE (or its depletion) to investigate the net effect of NE on adult hippocampal neurogenesis.…”
Section: Discussionmentioning
confidence: 99%